2019
DOI: 10.3390/su11226482
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Favourable Concept of Energy Retrofitting Solution for Social Housing in the Czech Republic Based on Economic Parameters, Greenhouse Gases, and Primary Energy Consumption

Abstract: Energy retrofitting of existing building stock has significant potential for the reduction of energy consumption and greenhouse gas emissions. Roughly half of the CO2 emissions from Czech building stock are estimated to be allocated to residential buildings. Approximately one-third of the Czech residential building stock have already been retrofitted, but retrofitting mostly takes place in large cities due to greater income. A favourable concept for the mass retrofitting of residential building stock, affordab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The increased peak demand for electricity in the summer, noted especially in recent years in Poland, can be ensured thanks to the use of photovoltaic panels as an energy source (Sobik, 2019). Following the example of Czech (Raport ERU, 2018;Pálenský and Lupíšek, 2019;Sojkova et al, 2019;Šerešová et al, 2020;Tanil and Jurek, 2020) and German (Fraunhofer Institute for Solar Energy Systems ISE, 2018), that is, in areas with similar insolation conditions, it can be concluded that the potential for the development of photovoltaics in Poland is significant and still unused.…”
Section: Directions Of Financing the Energy Production Growth From Renewable Sourcesmentioning
confidence: 99%
“…The increased peak demand for electricity in the summer, noted especially in recent years in Poland, can be ensured thanks to the use of photovoltaic panels as an energy source (Sobik, 2019). Following the example of Czech (Raport ERU, 2018;Pálenský and Lupíšek, 2019;Sojkova et al, 2019;Šerešová et al, 2020;Tanil and Jurek, 2020) and German (Fraunhofer Institute for Solar Energy Systems ISE, 2018), that is, in areas with similar insolation conditions, it can be concluded that the potential for the development of photovoltaics in Poland is significant and still unused.…”
Section: Directions Of Financing the Energy Production Growth From Renewable Sourcesmentioning
confidence: 99%
“…The previous sections demonstrated that the use of renewable materials in energy refurbishments in B&H and Slovenia is rather uncommon and remains off the radar of policymakers. Even if it is a relevant topic in different countries, with some successful technological solutions being developed (for example, TES, BERTIM, MORE-CONNECT, and CLT panel façade systems) [56][57][58]65], there has not been a general breakthrough leading to a wider use of such solutions in the analyzed countries. However, mentioned prefabricated solutions have significant potential, yet there are still gaps in understanding their possible use for energy refurbishment.…”
Section: Analysis Of the Barriers Preventing Wider Use Of Renewable Mmentioning
confidence: 99%
“…With respect to the fact that solutions like prefabricated panels can provide a higher standard of living and internal air quality since it integrates other services besides the thermal insulation function (e.g., mechanical ventilation, new heating piping, electrical wiring including Wi-Fi router), they can be considered beneficial from the point of view of sustainability and complex building stock retrofitting. On the other hand, such solutions have special requirements with regard to worker skills and expertise as techniques needed for assembling and completing the system are rather more complex compared to common practices [65].…”
Section: Analysis Of the Barriers Preventing Wider Use Of Renewable Mmentioning
confidence: 99%
“…A study by Deymi-Dashtebayaz et al [ 14 ] proved that an appropriately designed technological solution applying renewable energy sources can cover up to 70% and 57.9% of the electricity and heat demands, respectively. Therefore, a lot of authors appealing innovations and investment in energy efficiency technology remain significant in economic policy promoting [ 15 , 16 , 17 , 18 ]. A comprehensive review by Muteri et al [ 19 ] thoroughly described the results and modeling approaches of different photovoltaic panel studies, highlighting electricity consumption during manufacturing stage as the main part of the environmental burden.…”
Section: Introductionmentioning
confidence: 99%